Pengaruh Diet Ekstrak Protein Kedelai terhadap Glukosa Serum pada Tikus Diabetik Induksi Alloxan - Wisaniya N.W.; Yustinus Marsono; Zuheid Noor (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2002)
Hypoglycemic property of soyprotein extract were evaluated in alloxan-induced diabetic rats. The objectives of this research were to evaluate the effects of soyprotein extract feeding on glucose concentration in both normal-cholesterol and hypercholesterol alloxan-induced diabetic rats. Twenty-eight male Sprague-Dawley (SD) rats (250-300 g) were provided and divided into four groups of seven rats. They were (1) Standard-Placebo (SP). (2) Standard-Alloxan (SA), Soyprotein-Alloxan (PKA) and (4) Hypercholesterol-Soyprotein-Alloxan (HPKA) groups. Three groups were diabetic induced by alloxan injection (80 mg/Kg of body weught by intra-muscular injection) and one group (SP) was injected with aquabidest (placebo). HPKA groups were fed hypercholesterol diet 2 weeks prior to the alloxan injection. SP and HPKA were fed soy protein diet for 28 days. Concentration of serum glucose were determined before injection (0 day), 1,7, 14, 21, and 28 days after injection. It was found that alloxan injection increased serum glucose concentration of SA, PKA and HPKA rats. In 28 days intervertion, soybean protein diet decreased the serum glucose concentration from 405 mg/dL to 201mg/dL (50%) in PKA and from 428 mg/dL to 210 mg/dL (51%) in HPKA groups, but standard diets (SP and SA) were failed to decrease the serum glucose of the rats.